2019
DOI: 10.1371/journal.pone.0226005
|View full text |Cite
|
Sign up to set email alerts
|

RBM3 and CIRP expressions in targeted temperature management treated cardiac arrest patients—A prospective single center study

Abstract: BackgroundManagement of cardiac arrest patients includes active body temperature control and strict prevention of fever to avoid further neurological damage. Cold-shock proteins RNA-binding motif 3 (RBM3) and cold inducible RNA-binding protein (CIRP) expressions are induced in vitro in response to hypothermia and play a key role in hypothermia-induced neuroprotection.ObjectiveTo measure gene expressions of RBM3, CIRP, and inflammatory biomarkers in whole blood samples from targeted temperature management (TTM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…The GO and pathway enrichment analysis was of great importance for interpreting the molecular mechanisms of the key cellular activities in PCOS. RPS5 [ 37 ], RBM3 [ 38 ], BAK1 [ 39 ], NDUFC2 [ 40 ], NDUFS4 [ 41 ], NDUFS5 [ 42 ], UQCRFS1 [ 43 ], COX6B1 [ 44 ], NDUFA13 [ 45 ], PRMT1 [ 46 ], RDX (radixin) [ 47 ], EPHB4 [ 48 ], SYNE2 [ 49 ], DNAH5 [ 50 ], NEDD4L [ 51 ], PDE4B [ 52 ] and CTNND1 [ 53 ] plays a critical role in the process of cardiovascular disease, but these genes might be linked with development of PCOS. Ostergaard et al [ 54 ], Zi et al [ 55 ], Kunej et al [ 56 ], Van der Schueren et al [ 57 ], Jin et al [ 58 ], Emdad et al [ 59 ], Liu et al [ 60 ], Scherag et al [ 61 ], Shi and Long [ 62 ], Sharma et al [ 63 ], Parente et al [ 64 ], Saint-Laurent et al [ 65 ] and Lee [ 66 ] demonstrated that over expression of COA3, PHB (prohibitin), UQCRC1, COX4I1, IFI27, MTDH (metadherin), S100A16, SDCCAG8, GLI2, NTN1, NLGN2, FGFR3 and PTPRN2 could cause obesity, but these genes might be involved in progression of PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…The GO and pathway enrichment analysis was of great importance for interpreting the molecular mechanisms of the key cellular activities in PCOS. RPS5 [ 37 ], RBM3 [ 38 ], BAK1 [ 39 ], NDUFC2 [ 40 ], NDUFS4 [ 41 ], NDUFS5 [ 42 ], UQCRFS1 [ 43 ], COX6B1 [ 44 ], NDUFA13 [ 45 ], PRMT1 [ 46 ], RDX (radixin) [ 47 ], EPHB4 [ 48 ], SYNE2 [ 49 ], DNAH5 [ 50 ], NEDD4L [ 51 ], PDE4B [ 52 ] and CTNND1 [ 53 ] plays a critical role in the process of cardiovascular disease, but these genes might be linked with development of PCOS. Ostergaard et al [ 54 ], Zi et al [ 55 ], Kunej et al [ 56 ], Van der Schueren et al [ 57 ], Jin et al [ 58 ], Emdad et al [ 59 ], Liu et al [ 60 ], Scherag et al [ 61 ], Shi and Long [ 62 ], Sharma et al [ 63 ], Parente et al [ 64 ], Saint-Laurent et al [ 65 ] and Lee [ 66 ] demonstrated that over expression of COA3, PHB (prohibitin), UQCRC1, COX4I1, IFI27, MTDH (metadherin), S100A16, SDCCAG8, GLI2, NTN1, NLGN2, FGFR3 and PTPRN2 could cause obesity, but these genes might be involved in progression of PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…The GO and pathway enrichment analysis was of great importance for interpreting the molecular mechanisms of the key cellular activities in PCOS. RPS5 [37], RBM3 [38], BAK1 [39], NDUFC2 [40], NDUFS4 [41], NDUFS5 [42], UQCRFS1 [43], COX6B1 [44], NDUFA13 [45], PRMT1 [46], RDX (radixin) [47], EPHB4 [48], SYNE2 [49], DNAH5 [50], NEDD4L [51], PDE4B [52] and CTNND1 [53] plays a critical role in the process of cardiovascular disease, but these genes might be linked with development of PCOS. Ostergaard et al [54], Zi et al [55], Kunej et al [56], Van der Schueren et al [57], Jin et al [58], Emdad et al [59], Liu et al [60], Scherag et al [61], Shi and Long [62], Sharma et al [63], Parente et al [64], Saint-Laurent et al [65] and Lee [66] demonstrated that over expression of COA3, PHB (prohibitin), UQCRC1, COX4I1, IFI27, MTDH (metadherin), S100A16, SDCCAG8, GLI2, NTN1, NLGN2, FGFR3 and PTPRN2 could cause obesity, but these genes might be involved in progression of PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Показано, что RBM3 участвует в реализации эффектов нейропротекции, а представители БХШ рассматриваются как перспективные молекулы-прототипы новых лекарственных средств [30]. БХШ в нейрональной культуре снижает индуцированную оксидом азота гибель клеток, а понижение температуры корковых нейронов приводит к увеличению FGF21 и RBM3, что может предполагать наличие положительной связи и взаимодействия этих стрессбелков [31].…”
Section: молекулярные механизмы низкотемпературных технологийunclassified